The Influence Of Ease Of Use, Usefulness, Privacy Risk, And Government Support Towards Young Adult’s Usage Intention On mHealth During Covid-19 In Jakarta (Case Study On Halodoc) - Wardana, Elvina Nathania Sharon; Sihite, Janfry (International Humanities and Applied Science Journal, 2021)
This study aims to identify the perception of young adults during the COVID-19 pandemic that will influence their intention to use Halodoc application. This study examines factors from several theories such as Technology Acceptance Model and Theory Planned Behavior. The population of this research is young adults with an age range of 19-39 years, whether they have experienced or currently experiencing or have never experienced the COVID-19 symptoms, who are non-user yet know about Halodoc application. The sample used in this study was collected in around Jakarta with the total of 213 respondents. The sampling technique used is non probability and purposive sampling by using a quantitative descriptive approach. Analysis of the data used is statistical analysis in the form of SEMPLS. The results of this study indicate that perceived ease of use, perceived privacy risk, and government policy & support influence young adult usage intention of Halodoc application during this COVID-19 pandemic situation.Â